Characterization and identification of Trichoderma on shallots isolated from three elevation regions in West Sumatra, Indonesia - EKA SUSILA; FRI MAULINA; DENI EMILDA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Susila E, Maulina F, Emilda D. 2023. Characterization and identification of Trichoderma on shallots isolated from three elevation regions in West Sumatra, Indonesia. Biodiversitas 24: 2064-2071. Various microorganisms are found in the rhizosphere of plants. The species of Trichoderma exhibited many benefits to plants such as biological control of many crop diseases and their causing agents. This study aim was to explore, collect, and identify species of Trichoderma from shallot rhizosphere based on morphological characters and molecular techniques. The research was carried out from March to October 2021 at Biology Laboratories Agricultural State Polytechnic of Payakumbuh and Plant Protection Laboratory, Indonesian Tropical Fruits Research Institute (ITFRI) for morphological observation, and Molecular Laboratories, ITFRI for molecular identification. Samples were collected from Alahan Panjang (1700 m above sea level), Solok (400m asl) and Kambang (< 200 m asl) by using Stratified Random Sampling method. The isolates of Trichoderma species were cultured on Potato Dextose Agar (PDA). Three Trichoderma sp. from shallot rhizosphere were obtained and identified. Four specific primer pairs (T2A F-T2A R, T2 F-T2 R, T1 F-T1 R and Th1 F-Th1 R) were used for molecular identification. The amplification results of three isolates of Trichoderma spp. using four pairs of specific primers showed that the three isolates tested amplified only in the T. asperellum primer pair. The results showed that Trichoderma spp. origin of shallot rhizosphere from three locations (Alahan Panjang, Solok and Kambang) is identified as one species i.e. Trichoderma asperellum.